2016
DOI: 10.1038/npp.2016.96
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Early Life Stress, Nucleus Accumbens MeCP2 Expression, and Methamphetamine Self-Administration in Male Rats

Abstract: Early life stress (ELS) is highly related to the development of psychiatric illnesses in adulthood, including substance use disorders. A recent body of literature suggests that long-lasting changes in the epigenome may be a mechanism by which experiences early in life can alter neurobiological and behavioral phenotypes in adulthood. In this study, we replicate our previous findings that ELS, in the form of prolonged maternal separation, increases adult methamphetamine self-administration (SA) in male rats as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Maternal separation from PND 1–14 increases the rewarding effects of acute amphetamine exposure during adulthood, as measured by a decrease in intracranial self-stimulation current threshold ( Der-Avakian and Markou, 2010 ). Similar to findings following social isolation/social disruption, maternal separation results in greater methamphetamine self-administered and earlier acquisition while not altering extinction or cue-induced reinstatement ( Moffett et al, 2006 ; Lewis et al, 2013 , 2106 ). Exposure to maternal separation also has effects on alcohol and opiate intake and preferences during adulthood.…”
Section: Effects Of Early Life Adversity On Reward Processes and Drugsupporting
confidence: 65%
“…Maternal separation from PND 1–14 increases the rewarding effects of acute amphetamine exposure during adulthood, as measured by a decrease in intracranial self-stimulation current threshold ( Der-Avakian and Markou, 2010 ). Similar to findings following social isolation/social disruption, maternal separation results in greater methamphetamine self-administered and earlier acquisition while not altering extinction or cue-induced reinstatement ( Moffett et al, 2006 ; Lewis et al, 2013 , 2106 ). Exposure to maternal separation also has effects on alcohol and opiate intake and preferences during adulthood.…”
Section: Effects Of Early Life Adversity On Reward Processes and Drugsupporting
confidence: 65%
“…Although MeCP2 is known as gene silencer, recent evidence suggests it also binds to methylated non-CG sites ( Chen et al, 2015 ) and can function as a transcriptional activator by association with pCREB ( Chahrour et al, 2008 ). However, it is important to note a recent study that reported decreased METH SA after virally mediated knockdown of MeCP2 in the nucleus accumbens ( Lewis et al, 2016 ). These findings implicate potentially distinct roles of this protein in various brain regions following METH SA.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent finding is that ELS increases self-administration of various psychostimulants. For example, maternal separation increases active lever responses as well as the number of infusions of methamphetamine in male Long-Evans rats ( 111 , 112 ). Studies focused on cocaine largely find that ELS increases cocaine-seeking behaviors.…”
Section: Impact Of Early Life Stress On Motivated Behavior and Reward Circuit Activity From Non-human Animal Modelsmentioning
confidence: 99%